2020
DOI: 10.15390/eb.2020.8430
|View full text |Cite
|
Sign up to set email alerts
|

A New Model of Team Teaching for Teacher Professional Development: A Case Study of In-Service English Teachers

Abstract: * Bu makale Özlem Canaran'ın İsmail Hakkı Mirici danışmanlığında yürüttüğü "İngilizce öğretmenleri için bir sürekli mesleki gelişim modeli olarak takım öğretimine yeni bir bakış açısı" başlıklı doktora tezinden üretilmiştir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
0
11
0
4
Order By: Relevance
“…This sense of interest becomes the essential capital to raise the enthusiasm and motivation of students in learning so that learning objectives can be easily achieved. Several other research findings found that reading activities carried out in the science learning process supported the achievement of acquisition of scientific concepts (Cano, 2014;Romance, 2017;Rojas, 2019;Probosari, 2018;Canaran & Mirici, 2020). All these empirical studies proved that knowledge construction could be built precisely and scientifically through reading activities.…”
mentioning
confidence: 77%
“…This sense of interest becomes the essential capital to raise the enthusiasm and motivation of students in learning so that learning objectives can be easily achieved. Several other research findings found that reading activities carried out in the science learning process supported the achievement of acquisition of scientific concepts (Cano, 2014;Romance, 2017;Rojas, 2019;Probosari, 2018;Canaran & Mirici, 2020). All these empirical studies proved that knowledge construction could be built precisely and scientifically through reading activities.…”
mentioning
confidence: 77%
“…Innovation and organizational learning, according to Nawaz and Koç (2018), it is necessary to increase the capacity towards a sustainable organizational transition. Employee experience and skills influence the integration of new knowledge into organizational processes, which leads to innovation and increased organizational strength by providing the ability to overcome emerging challenges (Asif, Svensson et al 2011;Canaran & Mirici, 2020).…”
Section: Innovative Performancementioning
confidence: 99%
“…Human resource development is any positive process or activity that in the short or long term has the potential to develop knowledge based on work, expertise, profitability and satisfaction. Whether for individual, group, team or for the benefit of an organization, community, nation or ultimately all of humanity (Vanhala and Ahteela, 2010;Canaran & Mirici, 2020). Human resource development is a field of practice and theory that focuses on designing planned activities to facilitate learning and development in the organization in a way that benefits both the organization and learners (Lammintakanen & et al, 2008).…”
Section: Introductionmentioning
confidence: 99%